2007
DOI: 10.1111/j.1523-1739.2007.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Population Adaptive Index: a New Method to Help Measure Intraspecific Genetic Diversity and Prioritize Populations for Conservation

Abstract: In conservation biology genetic diversity is recognized as an important criterion to consider when prioritizing populations for protection. Today, population genomics offers the opportunity to evaluate both neutral and adaptive components of genetic diversity directly at the genome level with molecular tools. By screening the genome with many genetic markers, it is possible to detect loci supposedly under natural selection and thus of adaptive significance. We devised a new diversity index, the population adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
172
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(173 citation statements)
references
References 64 publications
0
172
0
1
Order By: Relevance
“…With recent advances in molecular technologies, it is anticipated that such information will become increasingly available. Moreover, loci under selection may allow for an estimation of the adaptive value of subpopulations, useful for conservation priorities (Bonin et al, 2007;Gebremedhin et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…With recent advances in molecular technologies, it is anticipated that such information will become increasingly available. Moreover, loci under selection may allow for an estimation of the adaptive value of subpopulations, useful for conservation priorities (Bonin et al, 2007;Gebremedhin et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…SNPs for example are often combined with microsatellites in population studies of marine organisms (Smith et al 2007;Narum et al 2008) because of their wider coverage of the genome, frequent association with genes and potential for large scale and cost effective genotyping (Seddon et al 2005;Nielsen et al 2009 and references therein). Also, SNPs associated with genes are more likely to be under the influence of selection and such loci are particularly useful in stock identification in fisheries and estimating the adaptive potential of metapopulations (Nielsen et al 2009;Bonin et al 2007). It is therefore important to apply appropriate tests of neutrality above and beyond measuring population structure (Rand 1996).…”
Section: Introductionmentioning
confidence: 99%
“…As expected from this perspective, levels of genetic subdivision for phenotypic traits are often higher than those for molecular markers (Spitze, 1993;Gockel et al, 2001;Storz, 2002;Steinger et al, 2002;Luttikhuizen et al, 2003;Volis et al, 2005;Schiffer et al, 2007). This approach has also been the basis for detecting subsets of potentially important loci, when using AFLP markers as genomic scans (Beaumont, 2005;Storz, 2005), with important implications for using genetics to set priorities in conservation (Bonin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The results from both B. vittatum and L. saxatilis highlight the potential usefulness of identifying not just individual traits that are adaptively important, but also significant environmental gradients. In their proposal to use genomic scans to identify markers associated with local adaptation, as a basis for assessing conservation priorities, Bonin et al (2007) also found greatest divergence associated with apparently important environmental gradients. Thus, although the emphasis has been on the identification of adaptively important traits, an important question for further work is how widely are independent traits adapted to the same environmental gradients.…”
Section: Biologically Significant Environmental Gradientsmentioning
confidence: 99%